2022
DOI: 10.3390/ijerph19052539
|View full text |Cite
|
Sign up to set email alerts
|

Asthma-Related Knowledge and Practices among Mothers of Asthmatic Children: A Latent Class Analysis

Abstract: Mothers’ knowledge about childhood asthma influences management practices and disease control, but validating knowledge/practice questionnaires is difficult due to the lack of a gold standard. We hypothesized that Latent Class Analysis (LCA) could help identify underlying mother profiles with similar knowledge/practices. A total of 438 mothers of asthmatic children answered a knowledge/practice questionnaire. Using answers to the knowledge/practice questionnaire as manifest variables, LCA identified two classe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 45 publications
3
15
1
Order By: Relevance
“…Additionally, Roncada et al [13] reported that parents of asthmatic children receive ample instructions and explanations from the treating doctors during their visits to the clinics and ED. Our results were consistent with those of previous studies by Fasola et al [9], BinSaeed [14], Urrutia-Pereira et al [21], AlOtaibi et al [22], Rastogi et al [23] regarding satisfactory caregiver awareness of the worsening effects of stopping asthma medications, having respiratory infections, and exposure to smoke and allergens.…”
Section: Caregivers Of Asthmatic Childrensupporting
confidence: 93%
“…Additionally, Roncada et al [13] reported that parents of asthmatic children receive ample instructions and explanations from the treating doctors during their visits to the clinics and ED. Our results were consistent with those of previous studies by Fasola et al [9], BinSaeed [14], Urrutia-Pereira et al [21], AlOtaibi et al [22], Rastogi et al [23] regarding satisfactory caregiver awareness of the worsening effects of stopping asthma medications, having respiratory infections, and exposure to smoke and allergens.…”
Section: Caregivers Of Asthmatic Childrensupporting
confidence: 93%
“…At class, she "hurts her lungs and struggles to breathe before she takes your inhaler because she thought she was placing an uncomfortable spotlight on her every time she used it. So an intelligent inhaler is necessary [33]. Breathable medicines are frequently used with a drug known as a measured dosage inhaler or MDI.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…A recent study (Fasola et al 2022) have used Latent Class Analysis (LCA) in mothers and concluded that LCA can help discover underlying mother profiles and plan targeted educational interventions. However, the severity of asthma was found to be significantly associated with the attitude and practice of mothers (Noureddin et al 2019).…”
Section: Association Between Demographic Characteristics and Mean Kno...mentioning
confidence: 99%
“…In the second section of the score (knowledge about asthma), the mean was significantly greater for the groups of parents who completed their university studies. They concluded that there was a significant correlation between level of education of parents and score of Asthma Knowledge Questionnaire, as the parents present with higher education can obtain knowledge easier, but despite of that most parents were highly educated but a lot of them have misconception and lack of information regarding use if inhalers and factors that triggering asthma of their children which necessitate to provide more effective education programmes Fasola et al (2022) studied mothers of asthmatics children answered a knowledge/practice questionnaire. The study hypothesized that Latent Class Analysis (LCA) could help identify underlying mother profiles with similar knowledge/practices.…”
Section: Introductionmentioning
confidence: 99%